Effect comparison of neuroendoscopy versus microsurgery in the treatment of lateral ventricular tumors - Li, Kai; Liang, Jianfeng; Niu, Hongchuan; Lan, Shuang; Liang, Xiaoning; Zhao, Yuanli; Zhao, Peng (Frontiers in Oncology, 2023)
Purpose We sought to reveal the clinical characteristics of lateral ventricle tumors and to evaluate the superior surgical procedure available. Methods There involved a total of of 49 adult patients harboring lateral ventricle tumors in neurosurgery department of our hospital from January 2016 to March 2022. The patients enrolled were retrospectively analyzed, so are their clinical manifestations, pathological characteristics and surgical strategies. The patients were allocated into neuroendoscope group (11 cases) and microsurgery group (38 cases) according to the operation method. The two groups underwent a detailed evaluation of operation effectiveness and safety profile (operation time, intraoperative bleeding, surgical resection rate, postoperative complications) and economic indicators (postoperative hospital stay, hospital costs). Results The neuroendoscope group demonstrated a markedly shorter operation time than the microsurgery group (p<0.05), with the amount of bleeding significantly less than the microsurgery group (p<0.01). However, there was no significant difference in the resection rate and postoperative complications between the two groups (p>0.05). Significant difference was found in the economic indicators (postoperative hospital stay and hospital costs) of the patients in the neuroendoscope group (p<0.05). Conclusion Surgery intervention is regarded as the core treatment option for lateral ventricle tumors. Both microsurgery and neuroendoscopy are effective with safety profile. In the selected lateral ventricle tumor surgery, the application of neuroendoscopic surgery showed promising results, in terms of less intraoperative bleeding, and shorter operation time, postoperative hospital stays, and hospital costs. The selection of surgical approach and methods for lateral ventricle tumors is principally depended on the experience of neurosurgeon concerning the surgical approach and related neuroanatomy.